Kendala Program Pemindahan Pemanfaatan Sarana Transportasi Pribadi Ke Publik Transpori' (TRANSJAKARTA) - Noviyanti, Noviyanti (Warta Penelitian Perhubungan, 2010)
Special Capital Region (D KI) Jakarta is surrounded bt; several cities that rome to support the eamomyof Bogar, Depok, Tangerang, and Bekasi. Eren; morning peak hours when congestion is difficul.t toavercome than tJwse cities to the D KI Jakarta. This happens because most people who work in the cityof Jakarta is located in tJwse cities. D KI Jakarta Prouincial Government's efforts to imprc:roe seroices tothe public using public transport Feroices such as Transjakarta has been cultivated as much as TXJSsiblesuch as steril:iz.a.tion lane lmsway. Hawever, it was less successful because most people who usepersonal rehicles do not want to switch to public transport such as Transjakmta. Related to the above,need to do ref£tl1'Ch on various things that cause the difficulty of transferring public using privatevehicles to public transport such as Transjakarta.Keywords: Tmasportasi Bus Way, Personal Vehicle